Pondasi Perkawinan Kristen: Membangun Keluarga dengan Kasih, Kesetiaan, dan Tanggung Jawab - Yakub Fransisko; Devi Lestary; Sarmauli Sarmauli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research begins with the complexity of challenges faced by Christian families in the modern era, such as issues of communication, loyalty, and role imbalance. The aim is to examine the theological meaning of marriage as a divine institution in Christianity, focusing on the core values ​​of love, loyalty, and responsibility. Furthermore, this research formulates implementative strategies to create a harmonious and strong Christian family. This research uses a descriptive qualitative approach with a literature study method, analyzing various biblical sources, books, and journals on Christian marriage. Data were analyzed by selecting, grouping, and summarizing the contents of the readings using a theological relational model, where love and loyalty are the foundation that gives rise to responsibility. The results show that Christian marriage is the embodiment of God's plan, a reflection of Christ's love, and the foundation for a harmonious family. Implementative strategies in modern life include: building communication based on love, maintaining loyalty in the digital age, implementing servant leadership and equal partnerships, making the family a community of faith, and managing conflict with forgiveness. This research is expected to strengthen Christian family life in the modern era through a deeper understanding of the theological meaning of marriage and the application of relevant practical strategies. Academically, this research contributes to the development of practical theology.